The Biblical Literary Tradition behind 'Nabouchodonosor who Ruled over the Assyrians' in Judith 1:1 - Korytiaková, Martina (Journal of septuagint and cognate studies, 2023)
The combination of anachronistic elements in the statement 'Nabouchodonosor who ruled over the Assyrians in Ninive' in Jdt 1:1 is no longer an interpretative problem. The expression has been explained by scholars as the author’s creation of the fictive paradigmatic enemy of the Jews as well as an indication of the story’s fictive character. Regarding the source of the combination of chronologically different components, exegetes point either to the author’s own creativity based on his knowledge of Israel’s history or to the non-biblical Greek influences. One may, however, wonder whether, by matching the heterogeneous elements, the author could not have followed a specific biblical literary tradition as well. The aim of the paper is, therefore, to show that the author’s choice to create the literary figure of the enemy with a Babylonian name and the Assyrian identity (1:1, 7, 11; 2:1, 4; 4:1) might have been informed by an existing tradition in biblical writings.